1994
DOI: 10.1002/bbpc.19940980706
|View full text |Cite
|
Sign up to set email alerts
|

Precise viscosity measurements of binary liquid mixtures of acetonitrile‐water and 1,3‐dimethyl‐2‐imidazolidinone‐water

Abstract: Viscosities of binary aqueous mixtures of Acetonitrile (AN) and 1,3-Dimethyl-2-imidazolidinone (Dimethylethyleneurea, DMEU) have been measured at atmospheric pressure and temperatures of 20, 25, 30, 35 and 40°C over the entire concentration region by means of Ubbelohde capillary viscometers, type Oc. For a set of 6 viscometers kinetic energy correction functions (Hagenbach-Couette correction) have been experimentally determined for each viscometer using tridistilled water and commercially available liquids. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…where l is the linear velocity of the eluent, g is the dynamic viscosity of eluent [51,52], L is the column length and DP is the pressure drop across the column. Good linear responses between back pressure and the linear flow rate for all six solvents (figure not shown) were observed, which clearly demonstrated that the monolith was mechanically stable and capable of withstanding pressures across the column of up to 35 MPa.…”
Section: Characteristics Of Poly(spv-co-mba) Monolithic Columnmentioning
confidence: 99%
“…where l is the linear velocity of the eluent, g is the dynamic viscosity of eluent [51,52], L is the column length and DP is the pressure drop across the column. Good linear responses between back pressure and the linear flow rate for all six solvents (figure not shown) were observed, which clearly demonstrated that the monolith was mechanically stable and capable of withstanding pressures across the column of up to 35 MPa.…”
Section: Characteristics Of Poly(spv-co-mba) Monolithic Columnmentioning
confidence: 99%
“…Their V E m curves for (DMI + methanol) and (DMI + ethanol) cross at x 1 % 0.27 and 0.74 and those for (DMI + propan-1-ol) and (DMI + butan-1-ol) cross at x 1 % 0.55. Furthermore, there is no systematic variation in composition (x 1 ) min of DMI at which V E m shows a minimum for (DMI + an alkan-1-ol); (x 1 ) min % 0.45, 0.31, 0.47, and 0.53 are, respectively, obtained for binary mixtures of DMI with [9]. f The value a p was evaluated from the density data in the temperature range from 283.15 K to 313.15 K tabulated in reference [11], assuming the density q is a linear function of temperature T: q/(kg AE m À3 ) = a + b(T/K).…”
Section: Resultsmentioning
confidence: 98%
“…The densities q of pure substances determined at T = (283.15, 298.15, and 313.15) K are listed in table 1 together with those found in the literature [2,9,11,12]. Temperature dependence of densities for each substance in the temperature range between 283.15 K and 313.15 K was correlated well with the following relation of the form: The experimentally determined densities q for binary mixtures of (DMI + an alkan-1-ol) over the whole composition range at three temperatures are summarized in table 2, where the V E m values calculated from the following equation are also given:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time limited studies on thermodynamic properties of aqueous DMI have been carried out and only a few papers on this problem are available in the literature [9,14,17,[26][27][28]. In the previous works [14,17], we have determined the values of standard (at infinite dilution) molar enthalpies of DMI solution, D sol H 2 , in H 2 O and D 2 O at various temperatures.…”
Section: Introductionmentioning
confidence: 98%